METODE BAYESIAN UNTUK DATA BINOMIAL DENGAN PENERAPANNYA PADA KASUS TIDAK RESPON - Sri Subanti (Program Studi Statistika Unisba, 2003)
Bayesian estimation methods for several binomial probabilities are studied by using a mixture of a product of betaprior distributions. Approximations to the posterior means and credible regions are derived. The result obtained are applied to asample survey problem in which there is significant nonresponse.